Asymmetric Price Responses of Gasoline Stations: Evidence for Heterogeneity of Retailers - Riemer P. Faber (Tinbergen Institute, 2009)
This paper studies asymmetric price responses of individual firms, via daily retail prices of almost all gasoline stations in the Netherlands and suggested prices of the five largest oil companies over more than two years. I find that 38% of the stations respond asymmetrically to changes in the spot market price. Hence, asymmetric pricing is not a feature of the market as a whole, but of individual firms. For asymmetrically pricing stations, the asymmetry is substantial directly after a change but disappears after one or two days. I study station-specific characteristics and conclude that asymmetric pricing seems to be a phenomenon that is randomly distributed across stations. I also find that none of the five largest oil companies adjust their suggested prices asymmetrically.
Keywords: D40; E31; L11; L81; 330; price setting; asymmetric price responses; gasoline markets; Tankstelle; Einzelhandelspreispolitik; Volatilität; Spotmarkt; Schätzung; Niederlande